PROJEKTY NOWYCH ROZWIĄZAŃ KONSTYTUCYJNYCH - Winczorek, Piotr (Wydział Prawa i Administracji UAM, 2006)
The paper is in the form of an essay devoted to an analysis o f two recent drafts containing an amended version of the constitution of the Republic of Poland, one authored by PiS (Law and Justice) party and the other by Samoobrona (Self-defence), as well as an analysis of certain amendments proposed by PO (Civil Platform). The analysis has focused on the general vision of the Polish State which emerges from the two drafts, and on the structure and the principles upon which Poland's main constitutional organs would function. PiS stance is that the Republic of Poland should take the form of a national state cultivating traditions and patriotic attitudes, and protecting and propagating Christian values. This, however, does not mean that Poland should transform itself into the “Catholic State of the Polish nation” . Both proposals, that of PiS and that of Samoobrona, contain solutions which advocate a fundamental change in the power vested in the President, proposing a substantial increase in the presidential competences. While PiS draft proposes maintaining the existing parliament-cabinet system, Samoobrona advocates a semi-presidential system. The paper discusses proposals regarding electoral law, the structure and functioning of parliament, and the legal status of the members of parliament. Much time is devoted to the relations between parliament (consisting of only one-chamber as proposed by Samoobrona) and the President and the Council of Ministers. The proposals advocating liquidation of certain constitutional organs, such as the National Council of Radio and Television Broadcasting and the Institution of the Ombudsman, and creation of new ones (eg. The Office of Assistance to the Victims of Injustice) have also been presented. The paper ends with a discussion of the possibilities of Constitutional amendments in the current political situation (2005/2006).
PROPOSALS OF NEW CONSTITUTIONAL SOLUTIONS